"If a Tree Falls …" : Posthuman Testimony in C. D. Wright's Casting Deep Shade. (2nd January 2020) - Connor, Eamonn
Abstract: During a period marked by profound ecological transformations, there has been surprisingly little consideration of how testimony may operate as a mediating discourse between human and nonhuman. Based on a close reading of C. D. Wright's "memoir" Casting Deep Shade, this article reconsiders the subject positions of witnessing in posthuman terms.